2018
DOI: 10.1177/2473011418782492
|View full text |Cite
|
Sign up to set email alerts
|

Online Patient Resources for Ankle Instability

Abstract: Background: The Internet has drastically changed how patients access health-related information. There are several ways the public can access online health-related information such as search engines, blogs, support groups, and webinars. A recent study found that 45% of orthopedic patients searched for information online regarding their injury. Also, 78% believed they had better understanding of their condition after visiting these websites; furthermore, 41% felt the Internet supplied them with questions and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…One study focusing on hallux valgus found that the average FKGL test score of available websites was 10.4, whereas another study focusing on ankle stability found an average FKGL test score of 10.1. 23,24…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study focusing on hallux valgus found that the average FKGL test score of available websites was 10.4, whereas another study focusing on ankle stability found an average FKGL test score of 10.1. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…The overall design and analysis utilized in this study was similar to that of previous studies in orthopedics focusing on pathologies other than ankle fractures. 21,22,24,26 The search terms Broken Ankle , Ankle Fracture , and Fibular Fracture were chosen to simulate the spectrum of vocabulary patients suffering from an ankle fracture may use when researching their diagnosis. The term Fibular Fracture was meant to adhere to stricter medical terminology, whereas Broken Ankle was meant to represent a layman’s description of the pathology.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations